(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article explores the prospects of implementing 5G technologies, spanning from medical safety aspects to their impact on sustainable development. It highlights the effects of electromagnetic radiation on human health, including medical recommendations and precautionary measures. Special attention is given to social and economic aspects such as bridging the digital divide, improving access to education and healthcare, developing smart cities, and energy-efficient technologies. The study addresses challenges related to cybersecurity and infrastructure while providing recommendations for the successful integration of 5G to achieve sustainable development goals.